Predominant Bacterial and Viral Otopathogens Identified Within the Respiratory Tract and Middle Ear of Urban Australian Children Experiencing Otitis Media Are Diversely Distributed - Ngo, Chinh C.; Massa, Helen M.; McMonagle, Brent A.; Perry, Christopher F.; Nissen, Michael D.; Sloots, Theo P.; Thornton, Ruth B.; Cripps, Allan W. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Otitis media (OM) is one of the most common infections in young children, arising from bacterial and/or viral infection of the middle ear. Globally, Streptococcus pneumoniae and non-typeable Haemophilus influenzae (NTHi) are the predominant bacterial otopathogens. Importantly, common upper respiratory viruses are increasingly recognized contributors to the polymicrobial pathogenesis of OM. This study aimed to identify predominant bacteria and viruses in the nasopharynx, adenoids and middle ears of peri-urban/urban South-East Queensland Australian children, with and without clinical history of chronic otitis media with effusion (COME) and/or recurrent acute otitis media (RAOM). Methods Sixty children, 43 diagnosed with OM and 17 controls with no clinical history of OM from peri-urban/urban South-East Queensland community were recruited to the study. Respiratory tract bacterial and viral presence were examined within nasopharyngeal swabs (NPS), middle ear effusions (MEE) and adenoids, using real-time polymerase chain reaction (RT-PCR) and bacterial culture. Results At least one otopathogen present was observed in all adenoid samples, 86.1% and 82.4% of NPS for children with and without OM, respectively, and 47.1% of the MEE from the children with OM. NTHi was the most commonly detected bacteria in both the OM and control cohorts within the adenoids (90.0% vs 93.8%), nasopharynx (67.4% vs 58.8%) respectively, and in the MEE (OM cohort 25.9%). Viruses were detected in all adenoid samples, 67.4% vs 47.1% of the NPS from the OM and control cohorts, respectively, and 37% of the MEE. Rhinovirus was the predominant virus identified in the adenoids (85.0% vs 68.8%) and nasopharynx (37.2% vs 41.2%) from the OM and control cohorts, respectively, and the MEE (19.8%). Conclusions NTHi and rhinovirus are predominant otopathogens within the upper respiratory tract of children with and without OM from peri-urban and urban South-East Queensland, Australia. The presence of bacterial otopathogens within the middle ear is more predictive of concurrent URT infection than was observed for viruses, and the high otopathogen carriage within adenoid tissues confirms the complex polymicrobial environment in children, regardless of OM history.